Assessing the Accuracy and Reproducibility of Computer‐Assisted Analysis of 123I‐FP‐CIT SPECT Using BasGan (V2). Issue 3 (16th January 2013) - Skanjeti, A.; Angusti, T.; Iudicello, M.; Dazzara, F.; Delgado Yabar, G. M.; Trevisiol, E.; Podio, V.
ABSTRACT BACKGROUND AND PURPOSE Over the last two decades 123I‐FP‐CIT‐SPECT, has been used to discriminate neurodegenerative Parkinsonian syndrome from other diseases. BasGan is a freely available software that assists 123I‐FP‐CIT‐SPECT evaluation by estimating semiquantitative values for each basal nucleus and compares the results to a database of healthy subjects. The aims of this study were: (1) to assess the accuracy of qualitative analysis and of semiquantitative, BasGan‐assisted evaluations of 123I‐FP‐CIT‐SPECT; (2) to compare the accuracy of both methods when applied to "doubtful" cases; (3) to appreciate the reproducibility of the BasGan‐assisted evaluations. MATERIALS AND METHODS Seventy‐eight patients were included in this 4‐year follow‐up study. The diagnostic cut‐off for semiquantitative uptake values of each basal nucleus was determined based on ROC curves analysis. Accuracy scores were calculated for the entire population and for "doubtful" cases. Intra‐ and interoperator reproducibility was assessed. RESULTS Accuracy of the software‐assisted analyses was high for data from each nucleus. In "doubtful" exams accuracy was higher when using BasGan as opposed to relying solely on visual assessment. Intra‐ and interoperator reproducibility of the BasGan‐assisted evaluations was good to excellent. CONCLUSION BasGan‐assisted evaluations of 123I‐FP‐CIT‐SPECT were very useful, particularly in "doubtful" cases. Multicenter studies are mandatory before routine use of BasGan.